Risk Assessment of Computer-Aided Diagnostic Software for Hepatic Resection - Akhtar, Yusuf; Dakua, Sarada Prasad; Abdalla, Alhusain; Aboumarzouk, Omar Mousa; Ansari, Mohammed Yusuf; Abinahed, Julien; Elakkad, Mohamed Soliman Mohamed; Al-Ansari, Abdulla (IEEE transactions on radiation and plasma medical sciences, 2022)
In this article, we study the indirect relationship between the adoption of computer-aided detection or diagnostic (CADe or CADx) systems for hepatic resection (HR) and the patient's health post-surgery. We vary the number, actual size, and the estimated size of tumors along with model parameters of tumor growth over 1000 simulations of HR according to predefined statistical distributions of parameter values. The average time ( t ) taken by the tumors to relapse is assessed for the nonadoption of computer-aided detection or diagnostic (CAD) (case 1), the adoption of semiautomatic CAD (case 2), and the adoption of automatic CAD (case 3) in HR. In this study, we have simulated 126 automatic CAD algorithms (case 3). For tumor volumes (TV) less than 50 cm 3 , if administration of bevacizumab, a post-operative therapy, is (not) adopted in the simulation, t is found to be 646, 84, and 60 days (40, 24, and 17 days) for case 1, case 2, and case 3, respectively. For TV greater than 50 cm 3 , and with (without) bevacizumab, t is found to be 86, 1, and 6 days (28, 6, and 3 days) for case 1, case 2, and case 3, respectively. For with (without) bevacizumab treatment and for all tumor volumes, t is found to be 260, 90, and 104 days (38, 13, and 11 days) for case 1, case 2, and case 3, respectively. We have observed that the tumors relapsed quickly in those cases where CAD was adopted.